Hello from MrBillDoesMath!
Answer:
One solution (z = -1)
Discussion:
-2(z+3)-z=-z-4(z+2) =>
-2z -6 -z = -z -4z - 8 =>
-3z -6 = -5z -8 => add 6 to both sides
-2z = -5z -2 => add 5z to both sides
3z = -5z +5z -3 =>
3z = -3 =>
z = -1
Thank you,
MrB
Answer:
x = -3
y = -8
Step-by-step explanation:
2y = x - 13
3x = y - 1; let y = 3x + 1
substitute to solve for 'x':
2(3x + 1) = x - 13
6x + 2 = x - 13
5x + 2 = -13
5x = -15
x = -3
solve for 'y':
3(-3) = y - 1
-9 = y - 1
-8 = y
Answer:
what is the answer
please tell me and explain
<span>Equation:
silver + silver = silver
0.45x + 0.60(40-x) = 0.48*40
----------------
45x + 60*40 - 60x = 48*40
--------
-15x = -12*40
x = (4/5)40
x = 32 lbs (amt of 45% slloy needed)
40-x = 8 lbs (amt of 60% alloy needed)</span>